R&D Management Practices and Innovation: Evidence from a Firm Survey - Haneda, Shoko (SpringerBriefs in Economics, 2022)
This Open Access book provides a detailed account of firms' research and development (R&D) management practices, and whether and how R&D management practices are associated with the success and the nature (explorative or exploitive) of innovation, using a unique survey of firms in Japan. While there is wide agreement that innovation is a key determinant for growth of firms, there are few studies that systematically and quantitatively investigate what firms do in their R&D management to create innovation. Utilizing insights from theoretical and empirical studies on innovation, the authors focus on the following four aspects of R&D management: the organizational structure of R&D, staged project management for R&D projects, compensation and incentive schemes for R&D personnel, and a firm's risk preferences and corporate culture. The authors examine whether and how R&D management practices are linked to the likelihood of firms' success in making product innovations and the choice between explorative and exploitive innovation. The book furnishes vital information that can be used as a reference for future theoretical and empirical analyses of R&D management practices and innovation. This monograph is highly recommended to academics and practitioners who seek an in-depth and detailed analysis of R&D management. This is an open access book.